An Examination of the Factors Influencing Afghan Migration to Iran and Its Consequences (Salam International Academic Journal, 2025)
Due to years of war, political instability, and economic poverty, Afghanistan has forced millions of its citizens into migration. Migrants have consistently sought economic opportunities, personal security, and better living conditions. Historically, Afghan migration has intensified as a result of political, social, and economic factors such as war, foreign intervention, natural disasters, and economic crises. Most of these migrations have been directed toward neighboring countries such as Iran and Pakistan, as well as to Central Asia, Turkey, and European countries. The growing scale of migration has not only posed challenges for migrants themselves but has also created significant difficulties for host countries. Understanding Afghan migration requires an in-depth examination of its social and political causes and their effects both inside and outside the country.This study investigates the factors influencing Afghan migration to Iran and the resulting consequences. Afghan migration to Iran is considered a significant regional phenomenon that has evolved over recent decades in response to political, economic, and social developments in Afghanistan, and it has produced multifaceted consequences for host countries. While push factors such as war, insecurity, and the collapse of economic infrastructure in Afghanistan have driven population outflows, pull factors such as geographic proximity, linguistic and cultural similarities, and economic opportunities in Iran have played a decisive role in attracting these migrants.The research method used in this study is descriptive and analytical, conducted qualitatively and based on library research. Data collection relied on credible academic sources, reports from national and international institutions, and other reputable references. The study then analyzes the factors and consequences of migration to Iran, and the findings are presented descriptively. The results of this study indicate that a variety of economic, social, political, and security factors have contributed to the expansion of migration from Afghanistan to other countries, especially its neighbors, and have continuously generated challenges for both migrants and destination countries. Therefore, the Afghan government can contribute to improving conditions for migrants and reducing social tensions in host societies by formulating coherent and coordinated policies. Achieving this goal requires collaboration among domestic institutions responsible for migration management and coordination with international service organizations and host countries.
Keywords: Afghan Migration; Migration Drivers; Migration Consequences; Afghanistan; Iran